A case study of four beginning teachers' experience, workplace challenges and support received in the first year of teaching / Maheran Mohd Yusoff - Mohd Yusoff, Maheran (2005)
The purpose of this study was to analyse the beginning teachers' experience, the challenges met and the support received in the first year of real classroom teaching. It also sought to exploit on how support and assistance could be given to help them function as new members in the school culture. The respondents consisted of four KPLI English language beginning teachers from four districts in Kelantan. The respondents were purposively selected and they also were the graduates of the same teachers training college in the East Coast. The respondents' views and answers were obtained through an in-depth semi-structured interview phased within the limited duration of two weeks. The data were analyzed qualitatively and presented thematically. The findings showed that even at an early stage of their career, some concerns had already surfaced from beginning teachers because of the pure desire to give optimum input and total commitment to the profession. The revelation was very useful in understanding the beginning teachers' apprehension about the profession in relation to certain issues that took place in schools. Lessons learned from this research will be useful for future professional teacher development programmes. The suggestions made by the beginning teachers are worth looking into, especially by the school administrators and educational experts and specialists in order to improve the education of the country.